Marketing Innovation in the Digital Communication Era - Jihan Afifah Wahyu Aroyssi; Maulana Raihan Fathin; Yudis Ilmi Priabas (International Journal of Research and Applied Technology (INJURATECH), 2022)
This research is motivated by the presence of E-Commerce which attracts customers by providing many discounts and providing easy access to customers. Both hardware (mobile phone use) and software (easy access to applications). The purpose of this research is to understand and identify technological developments in the digital era, especially in the field of digital transactions. Seeing the many marketplaces that are developing and enlivening the national and international markets. It also has an impact on marketing communications, which have now begun to switch to digital. The research method used is the study of literature from various journals and previous research. Also interviews from parties involved in every marketing communication activity in the digital era. Such as technology developers, traders, marketing agents and consumers. Meanwhile, the benefits that will be obtained are, being research material for technology developers in the digital era and easy access to marketing communications for micro and macro businesses.